2010
DOI: 10.1002/lary.21089
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus and WHO type I nasopharyngeal carcinoma

Abstract: Objectives Nasopharyngeal carcinoma (NPC) is a rare cancer in the United States. An association between NPC and Epstein-Barr virus (EBV) is well-established for World Health Organization (WHO) types II and III (WHO-II/III) NPC but less well-established for WHO type I (WHO-I) NPC. Given the rise in oropharyngeal tumors positive for high-risk human papillomavirus (HPV) and the unique biology of WHO-I NPC, we examined the relationship between HPV and WHO-I NPC. Study Design Retrospective case-comparison study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 34 publications
3
64
0
1
Order By: Relevance
“…Also, of the latter four studies18 23–25 from areas non-endemic for NPC and including HPV-positive WHO-I NPCs, only one18 found co-infection of EBV in HPV-positive WHO-I NPCs. In contrast, of the six studies13 18 19 22 24 25 from non-endemic areas including HPV-positive WHO-II/III NPCs, four13 18 22 24 showed co-existence of EBV in HPV-positive WHO-II/III NPC cases. Thus, in both endemic and non-endemic areas, HPV infection occurs more commonly in WHO-I NPCs than in WHO-II/III NPCs.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Also, of the latter four studies18 23–25 from areas non-endemic for NPC and including HPV-positive WHO-I NPCs, only one18 found co-infection of EBV in HPV-positive WHO-I NPCs. In contrast, of the six studies13 18 19 22 24 25 from non-endemic areas including HPV-positive WHO-II/III NPCs, four13 18 22 24 showed co-existence of EBV in HPV-positive WHO-II/III NPC cases. Thus, in both endemic and non-endemic areas, HPV infection occurs more commonly in WHO-I NPCs than in WHO-II/III NPCs.…”
Section: Discussionmentioning
confidence: 72%
“…Also, compared with HPV-positive WHO-II/III NPCs, HPV-positive WHO-I NPCs are less likely to be EBV-positive. These observations raise the possibility that HPV infection may be important in the pathogenesis of some EBV-negative WHO-I NPCs 19 25. Further investigations are required to clarify this issue.…”
Section: Discussionmentioning
confidence: 94%
“…The reported incidence of HPV in NPC ranges from 9–52.9% [8-10,12-14]. Although this wide range may be attributed to differences in geographic variation with regard to aetiology and prevalence of NPC, it is more likely a result of non-standardised viral detection methods.…”
Section: Discussionmentioning
confidence: 99%
“…Although both low-risk and high-risk HPVs (6, 11, 16, and 18) were detected, HPV16 and 18 were more prevalent, accounting for 66.7% of HPV-positive NPC tumors in a Chinese cohort (Tung et al, 1999). In contrast, co-infections were rarely detected in NPC from non-endemic areas (Stenmark et al, 2014), and several studies have suggested that HPV and EBV appear to be mutually exclusive in NPC with oncogenic HPV types 16, 18, 39, 45, and 59 only detected in EBV-negative NPC (Dogan et al, 2014; Lin et al, 2014; Lo et al, 2010; Maxwell et al, 2010; Robinson et al, 2013). The presence of EBV or HPV in NPC correlated with an overall improved survival compared to virally-negative NPC, a similarity noted for HPV-positive OSCC (Dogan et al, 2014; Stenmark et al, 2014).…”
Section: Hpv and Herpesvirusesmentioning
confidence: 99%